Cenário do licenciamento ambiental: principais entraves - análise das competências ambientais no sistema federativo brasileiro - Saito, Estela Rosa Federmann (2010)
The disorder growth of the industries, since the 1970s, raised environmental laws which control the pollution by environmental agencies. Then, it was created the environmental permit, one of the instruments of National Environmental Policy, with the purpose to maintain sustainability. With the environmental criminal law edition, the environmental permit begins to be more relevant, because it became a crime not having a permit in an undertaking. It is an extremely instigate subject, because it involves different actors, such as public agencies, industries, Executive, Legislative, Judiciary Power, and the society itself. The importance of the subject is obvious when it is verified, by IBAMA information, that it has been demanded by the business man billions named as environmental impacts mitigation, beyond compensatory measures. Therefore, the reader is invited to an approach of the legal structure, such as legal as well as principle structure, which involves environmental permit, environmental competence, main issue of our dissertation, and of the several of obstacles that damage, sometimes, make impossible the installation and the operation of activities and industries, that potentially or effectively cause environmental impact in Brazil